Pengaruh Kepuasan Kerja, Komitmen Organisasi, Dan Kompleksitas Tugas Terhadap Turnover Intention Pada Kantor Akuntan Publik - Ardimeranti, Kartika; Suryaningsih, Rosita (Ultimaccounting Jurnal Ilmu Akuntansi, 2012)
The purpose of this research is to determine the impact of job satisfaction, organizational commitment, and task complexity towards turnover intention in public accountant firms. The respondents of the research are junior auditors, senior auditors, supervisors, and managers in public accountant firms in Jakarta and Tangerang. The samples were taken by non-probability sampling method by using convenience sampling. The total samples used in analysis are 130 respondents. Data analysis conducted by using multiple regressions. Data quality test in this research is validity test by using Pearson correlation, reliability test by using cronbach's alpha, normality test using normal probability plot. Classical asumptions test in this research is multicollonierity test by using tolerance and variance inflation factor (VIF) ans heteroscedasticity test by using scatterplot. The result of hypothesis testing showed that job satisfaction, organizational commitment, and task complexity as simultaneously have significant influence towards turnover intention. Meanwhile, only job satisfaction and organizational partially has significant influence towards turnover intention. Task complexity has no significant influence towards turnover intention. Keywords: job satisfaction, organizational commitment, task complexity, turnover intention.